Higienismo e educação nas páginas de O Ateneu - Bercho, Carolina Fuzaro (2011)
This text analyzes the schooling process in Brazil during se XIX century, questioning the formation of secondary education on the Empire of the Court. Rather, the discourse for the education, set within the broad project of social intervention, made by the medical corporation. Aiming to examine more precisely the representations medicalhygienic, we used two tipes os sources: two theses by graduating in medicine from the mid XIX century, and the romance of memories: O Ateneu, written by the intellectual Raul Pompéia in 1888. Aiming to examine the proposal set out in the literature in conjunction with the medical-civilizing project for youth in Rio de Janeiro, as well as highlight the importance of hygiene and the orientation mechanism of the everyday practices of school time.